Molecular mechanisms of paralogous compensation and the robustness of cellular networks. Issue 7 (24th December 2013) - Diss, Guillaume; Ascencio, Diana; DeLuna, Alexander; Landry, Christian R.; Peisajovich, Sergio G.; Thattai, Mukund
ABSTRACT Robustness is the ability of a system to maintain its function despite environmental or genetic perturbation. Genetic robustness is a key emerging property of living systems and is achieved notably by the presence of partially redundant parts that result from gene duplication. Functional overlap between paralogs allows them to compensate for each other's loss, as commonly revealed by aggravating genetic interactions. However, the molecular mechanisms linking the genotype (loss of function of a gene) to the phenotype (genetic buffering by a paralog) are still poorly understood and the molecular aspects of this compensation are rarely addressed in studies of gene duplicates. Here, we review molecular mechanisms of functional compensation between paralogous genes, many of which from studies that were not meant to study this phenomenon. We propose a standardized terminology and, depending on whether or not the molecular behavior of the intact gene is modified in response to the deletion of its paralog, we classify mechanisms of compensation into passive and active events. We further describe three non‐exclusive mechanisms of active paralogous compensation for which there is evidence in the literature: changes in abundance, in localization, and in protein interactions. This review will serve as a framework for the genetic and molecular analysis of paralogous compensation, one of the universal features of genetic systems. J. Exp. Zool. (Mol. Dev. Evol.) 322B: 488–499, 2013. © 2013 Wiley Periodicals, Inc.